Membrane Receptor-Induced Changes of the Protein Kinases A and C Activity May Play a Leading Role in Promoting Developmental Synapse Elimination at the Neuromuscular Junction - Tomàs, Josep M.; Garcia, Neus; Lanuza, Maria A.; Nadal, Laura; Tomàs, Marta; Hurtado, Erica; Simó, Anna; Cilleros, Víctor (Frontiers in Molecular Neuroscience, 2017)
Synapses that are overproduced during histogenesis in the nervous system are eventually lost and connectivity is refined. Membrane receptor signalling leads to activity-dependent mutual influence and competition between axons directly or with the involvement of the postsynaptic cell and the associated glial cell/s. Presynaptic muscarinic ACh autoreceptors (subtypes mAChR; M1, M2 and M4), adenosine receptors (AR; A1 and A2A) and the tropomyosin-related kinase B receptor (TrkB), among others, all cooperate in synapse elimination. Between these receptors there are several synergistic, antagonic and modulatory relations that clearly affect synapse elimination. Metabotropic receptors converge in a limited repertoire of intracellular effector kinases, particularly serine protein kinases A and C (PKA and PKC), to phosphorylate protein targets and bring about structural and functional changes leading to axon loss. In most cells A1, M1 and TrkB operate mainly by stimulating PKC whereas A2A, M2 and M4 inhibit PKA. We hypothesise that a membrane receptor-induced shifting in the protein kinases A and C activity (inhibition of PKA and/or stimulation of PKC) in some nerve endings may play an important role in promoting developmental synapse elimination at the neuromuscular junction. This hypothesis is supported by: i) the tonic effect (shown by using selective inhibitors) of several membrane receptors that accelerates axon loss between postnatal days P5-P9, ii) the synergistic, antagonic and modulatory effects (shown by paired inhibition) of the receptors on axonal loss, iii) the fact that the coupling of these receptors activates/inhibits the intracellular serine kinases and, iv) the increase of the PKA activity, the reduction of the PKC activity or, in most cases, both situations simultaneously that presumably occurs in all the situations of singly and paired inhibition of the mAChR, AR and TrkB receptors. The use of transgenic animals and various combinations of selective and specific PKA and PKC inhibitors could help to elucidate the role of these kinases in synapse maturation.